2022
DOI: 10.3390/metabo12060500
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Determinants in Cardiomyocyte Function and Heart Regenerative Strategies

Abstract: Heart disease is the leading cause of mortality in developed countries. The associated pathology is characterized by a loss of cardiomyocytes that leads, eventually, to heart failure. In this context, several cardiac regenerative strategies have been developed, but they still lack clinical effectiveness. The mammalian neonatal heart is capable of substantial regeneration following injury, but this capacity is lost at postnatal stages when cardiomyocytes become terminally differentiated and transit to the fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 205 publications
0
5
0
Order By: Relevance
“…A cessation of mitochondrial fission is additionally required for cardiomyocyte differentiation ( 98 ). The critical nature of these changes (demonstrated both in rodent models and stem cell models of cardiac development) may explain the potential role for CLUH in TOF pathogenesis, as a lack of cardiac differentiation would explain the structural defects that define TOF ( 99 ). An alternative hypothesis is that mitophagy has also been demonstrated to begin upon differentiation of stem cells to cardiac progenitors and is necessary for proper mitochondrial network formation, cellular stress response and cell survival ( 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cessation of mitochondrial fission is additionally required for cardiomyocyte differentiation ( 98 ). The critical nature of these changes (demonstrated both in rodent models and stem cell models of cardiac development) may explain the potential role for CLUH in TOF pathogenesis, as a lack of cardiac differentiation would explain the structural defects that define TOF ( 99 ). An alternative hypothesis is that mitophagy has also been demonstrated to begin upon differentiation of stem cells to cardiac progenitors and is necessary for proper mitochondrial network formation, cellular stress response and cell survival ( 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Correia et al, 2022) spotlight important research of nutrient signaling and metabolism in cardiomyocyte function, together with insights into metabolic reprogramming for the duration of improvement and withinside the injured coronary heart. Additionally discussed the key metabolic determinants and manipulations that drive cellular pluripotency and cardiac differentiation that have been proven to enhance cutting‐edge coronary heart regenerative strategies.…”
Section: Dynamics Of Metabolismmentioning
confidence: 99%
“…Figure2represents the general metabolic process of cardiomyocytes.Another Study reported that mitochondrial biogenesis is necessary for maturation of cardiomyocytes and revealed a new strategy to improve the PSC-CMs maturation and therefore to generate more physiologically mature CMs for disease modeling, drug screening, and therapeutic purposes, while mitochondrial dynamics also play important roles in cardiac development. Manipulating mitochondrial fission and fusion can be one of the feasible approaches to enhance the maturation of CMs(Ding et al, 2021) (Correia et al, 2022). spotlight important research of nutrient signaling and metabolism in cardiomyocyte function, together with insights into metabolic reprogramming for the duration of improvement and withinside the injured coronary heart.…”
mentioning
confidence: 99%
“…For example, energy utilization switches from glycolysis in early development to oxidative phosphorylation in matured cardiomyocytes. The differentiation of cardiomyocytes from the cardiac mesoderm also involves the establishment of cell–cell coupling, sarcomere assembly, and metabolic shifts that are necessary for the development of fully functioning heart muscles with synchronized contractile activity [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%